PWE-246 Infliximab treatment significantly reduces inflammatory macrophage numbers while preserving regulatory macrophages in a mouse model of chronic Crohn's colitis. (28th May 2012) - Levison, S; Little, M C; Grencis, R K; McLaughlin, J T; Pennock, J L
Abstract : Introduction: Inappropriate inflammatory responses to intestinal flora, augmented by host susceptibility genetics, contribute to the pathogenesis of Crohn's disease (CD). Transmural intestinal inflammation results from innate and adaptive immune cell infiltration, and pro-inflammatory cytokine accumulation. Activated macrophages represent a major source of TNFα production. The treatment of CD with anti-TNFα antibody (Ab) therapy has proved clinically beneficial, yet over 30% of patients fail to respond. We characterised the biological and immunological effects of Infliximab therapy in a model of experimental colitis. Methods: Genetically identical mice (AKR), susceptible to chronic Trichuris muris -induced colitis, were infected with 300 T muris eggs. A single 5 mg/kg dose of Infliximab was administered intra-peritoneally once chronic colitis had established (from day 35 post-infection, p.i.). Systemic, mesenteric lymph node (MLN) and colonic effects were analysed at day 45 p.i. MLN cell cytokine bead-array and colonic gene expression (RT-qPCR) analysis were performed. Colonic histopathology, tissue Foxp3 +, and macrophage recruitment and phenotype were determined. The treatment group was compared to untreated-infected, naive, and naïve AKR administered Infliximab (n=5 per group). Results: Treatment did not alter worm expulsion. Anti–TNFα Ab therapy preserved colonic length compared to untreated disease (p=0.049). Colonic inflammation was less severe with Infliximab treatment (p=0.07). Reduced TNFα, CCL2, and GMCSF proteins were measured in the MLN of Infliximab treated infected AKR. Reduced colonic expression of TNFα, IL-1β, IFNγ and IL-12p40, and increased IL-13 was observed following Infliximab treated disease. Colonic Foxp3 + cell numbers increased with disease but were unaltered by treatment. Infected mice treated with Infliximab demonstrated a 50% reduction in colonic F4/80 + macrophages (p=0.036). A relative increase of the proportion of colonic Arg + alternatively activated macrophages (AAMФ) was observed with Infliximab treatment compared to untreated disease (29% vs 14%). Conclusion: Infliximab therapy suppresses TH1-driven experimental colitis. Anti–TNFα Ab treatment reduced pro-inflammatory macrophages recruitment, and for the first time in vivo has been shown to preserve colonic tissue regulatory AAMФ. Whether a result of a fundamental alteration to macrophage recruitment, or the differentiation of a specific macrophage phenotype, requires further study. The presence of AAMФ at index biopsy, or an increase in AAMФ numbers following treatment initiation, may help to identify patient responders to Anti-TNFα Ab therapy. Competing interests: None declared.